Mechanisms of acquired resistance to targeted cancer therapies. (August 2012) - Lackner, Mark R; Wilson, Timothy R; Settleman, Jeff
Drugs that target genomically defined vulnerabilities in human tumors have now been clinically validated as effective cancer therapies. However, the relatively rapid acquisition of resistance to such treatments that is observed in virtually all cases significantly limits their utility and remains a substantial challenge to the clinical management of advanced cancers. As molecular mechanisms of resistance have begun to be elucidated, new strategies to overcome or prevent the development of resistance have begun to emerge. In some cases, specific mutational mechanisms contribute directly to acquired drug resistance, and in other cases it appears that nonmutational and possibly epigenetic mechanisms play a significant role. This article discusses the various genetic and nongenetic mechanisms of acquired drug resistance that have been reported in the context of 'rationally targeted' drug therapies.